PLASMA PROTEIN Z CONCENTRATIONS IN PREGNANT WOMEN WITH IDIOPATHIC INTRAUTERINE BLEEDING AND IN WOMEN WITH SPONTANEOUS PRETERM LABOR - Kusanovic, Juan Pedro (2007)
OBJECTIVE: Preterm parturition has been associated with decidual vascular disorders and excessive thrombin generation. The objective of this study was to examine maternal plasma concentrations of protein Z in normal pregnancies, as well as in those presenting with spontaneous preterm labor (PTL) and intrauterine bleeding during pregnancy. STUDY DESIGN: A cross-sectional study was designed to include patients with preterm labor and intact membranes and those with idiopathic intrauterine bleeding during pregnancy. Protein Z plasma concentrations were measured in the following groups: 1) normal pregnant women (n=71); 2) patients at term with (n=67) and without labor (n=88); 3) patients with spontaneous PTL before 34 weeks who were classified into: a) PTL with intra-amniotic infection/inflammation (IAI; n=35), b) PTL without IAI (n=54), and c) patients with PTL who delivered at term (n=49); and 4) patients with idiopathic intrauterine bleeding in the second and third trimester who were divided into: a) subsequent spontaneous PTL and delivery, and b) term delivery. Maternal plasma protein Z concentration was measured by a specific and sensitive immunoassay. Moreover, the amniotic fluid concentration of protein Z was determined in a subset of patients with preterm labor (n=30). RESULTS: 1) There was no correlation between maternal plasma protein Z concentration and gestational age in normal pregnant women. 2) The mean maternal plasma concentration of protein Z was significantly lower in women during spontaneous labor at term than in those not in labor [mean: 2.15 μg/mL (95% CI: 2.01-2.29) vs. mean: 2.45 ± 0.52 μg/mL (95% CI: 2.34-2.56), respectively; p=0.001]; 3) Women with PTL without IAI who delivered preterm had a significantly lower mean protein Z concentration than normal pregnant women [mean: 2.12 μg/mL (95% CI: 1.98-2.26) vs. mean: 2.39 μg/mL (95% CI: 2.28-2.5); p=0.008); 4) Of interest, PTL with IAI was not associated with lower plasma concentrations of protein Z, nor were those with PTL who delivered at term (p>0.05 for each); 5) No differences were found in the maternal plasma concentrations of anti-protein Z antibodies between normal pregnancies and those with spontaneous PTL; 6) Patients with idiopathic intrauterine bleeding who had spontaneous PTL and delivery had a significantly lower mean plasma protein Z concentration than those who delivered at term [mean: 1.24 μg/mL (95% CI: 1.08-1.4) vs. mean: 1.49 ± 0.47 μg/mL (95% CI: 1.33-1.65), respectively; p=0.03]; and 7) Amniotic fluid was found to contain immunoreactive protein Z. CONCLUSIONS: 1) Patients with PTL leading to preterm delivery in the absence of IAI had a significantly lower plasma concentration of protein Z than those with normal pregnancies; 2) Patients with idiopathic intrauterine bleeding and subsequently spontaneous PTL and delivery had a significantly lower plasma concentration of protein Z than those with idiopathic intrauterine bleeding who delivered at term; and 3) Protein Z was present in the amniotic fluid of patients with PTL. Collectively, these observations suggest that a subgroup of patients with PTL have a haemostatic disorder which involves bleeding/thrombosis as a mechanism of disease.